کیرن آرمسٹرانگ کی کتاب "محمد: آ پرافٹ آف آور ٹائم": 21ویں صدی کے چیلنجزکےتناظر میں ایک مطالعہ: Karen Armstrog’s book “Muhammad: A Prophet of our Time”: An Analytical Study in the Context of the Challenges of 21st Century (Al-Qamar, 2021)
An orientalist is a non-Muslim who is an expert in oriental studies. Orientalism is the study of Eastern values, Culture, Art, and the Religion of Islam by a non-Muslim of the West. Most orientalists criticized Islam. Karen Armstrong is also an orientalist but author tried to show the real image of Islam in the west. Her book “Muhammad: A Prophet of our Time” is an analytical study of the biography of Holy Prophet SAW. She made five chapters named: 1. Mecca, 2. Jahilliyah, 3. Hijrah, 4. Jihad, and 5. Salam. She tried to make a positive analysis but sometimes she misunderstood some situations. She also advised other orientalists to be moderate. In the last, she explained some Islamic terminologies and also add images of the cities discussed in the book. So, I analyzed her book and also tried to explain her misunderstandings.
Keywords: Karen Armstrog; book Muhammad; Prophet; Challenges; 21st century